Regulation of tissue growth in plants – A mathematical modeling study on shade avoidance response in Arabidopsis hypocotyls - Favre, Patrick; van Schaik, Evert; Schorderet, Martine; Yerly, Florence; Reinhardt, Didier (Frontiers in Plant Science, 2024)
Plant growth is a plastic phenomenon controlled both by endogenous genetic programs and by environmental cues. The embryonic stem, the hypocotyl, is an ideal model system for the quantitative study of growth due to its relatively simple geometry and cellular organization, and to its essentially unidirectional growth pattern. The hypocotyl of Arabidopsis thaliana has been studied particularly well at the molecular-genetic level and at the cellular level, and it is the model of choice for analysis of the shade avoidance syndrome (SAS), a growth reaction that allows plants to compete with neighboring plants for light. During SAS, hypocotyl growth is controlled primarily by the growth hormone auxin, which stimulates cell expansion without the involvement of cell division. We assessed hypocotyl growth at cellular resolution in Arabidopsis mutants defective in auxin transport and biosynthesis and we designed a mathematical auxin transport model based on known polar and non-polar auxin transporters (ABCB1, ABCB19, and PINs) and on factors that control auxin homeostasis in the hypocotyl.In addition, we introduced into the model biophysical properties of the cell types based on precise cell wall measurements. The model can generate the observed cellular growth patterns based on auxin distribution along the hypocotyl resulting from production in the cotyledons, transport along the hypocotyl, and general turnover of auxin. These principles, which resemble the features of mathematical models of animal morphogen gradients, allow to generate robust shallow auxin gradients as they are expected to exist in tissues that exhibit quantitative auxindriven tissue growth, as opposed to the sharp auxin maxima generated by patterning mechanisms in plant development.ABCB ATP-binding cassette (ABC) transporter subfamily B DR5::GUS ß-glucuronidase under the control of the auxin-inducible DR5 promoter SAS Shade avoidance syndrome FR Far red light R:FR ratio Ratio of red light vs. far red light PAT Polar auxin transport PIN Pin-formed CL75/130 Continuous light at 75/130 µE = 75/130 µmol•m -2 •s -1 LD75/130 Long days at 75/130 µE = 75/130 µmol•m -2 •s -1